QI initiative to reduce the number of inpatient falls in an acute hospital Trust. Issue 1 (3rd February 2023) - Boot, Michelle; Allison, Jennifer; Maguire, Jack; O'Driscoll, Gemma
Abstract : Inpatient falls are one of the most frequent concerns to patient safety within the acute hospital environment, equating to 1700 falls per year in an 800-bed general hospital. They are predicted to cost approximately £2600 per patient, however, this estimate does not capture the costs and impact that inpatient falls have on the wider health and social care system. It also does not take into the account loss of confidence and delays in functional recovery. This report shares the learning from a quality improvement (QI) initiative that took place in a District General Hospital (DGH) in the UK. The initiative started in February 2020, was paused November 2020 due to wave 2 of the pandemic and restarted in March 2021. Improvement was achieved in January 2021. Data for falls within the Trust identified that falls were within common cause variation. A system change was needed to achieve an improvement. A QI project was commenced with the aim to achieve a 5% reduction in falls per 1000 bed days in a care of the elderly ward. Two primary drivers were identified: recognising patients at high risk of falls and preventing them from falling. Change ideas to address these primary drivers were tested using Plan Do Study Act (PDSA) cycles. Changes tested included: the development of an assessment tool to identify patients at high risk of falls, use of a wristband to identify patients at high risk of a fall, and increased observation. Change ideas achieved some success with the process measures but did not achieve an improvement with the outcome measures. A Trust wide change idea relating to the falls prevention service did lead to a sustained improvement in falls reduction. The barriers to the improvement included changing Trust priorities during the pandemic, and limited opportunities to fully engage the ward-based team with systems thinking and changing mental models.